1569 Cardiac Involvement in young Infants with Sepsis-Like Illness is not Associated with Enterovirus Infection. (October 2012) - Jong, EP De; Filippini, LHPM; Elzakker, EPM Van; Walther, FJ; Brus, F
Abstract : Introduction: Enterovirus (EV) infection is common in young infants, amongst those admitted to intensive care units acute myocarditis has been reported. We questioned if myocardial involvement exists in less seriously ill children with EV infection. Methods: From august 2011 onward we included children under 90 days of age, who were admitted to our hospital for sepsis-like illness. During admission serum concentrations of Troponine-I, CK, CK-MB, BNP and NT-Pro-BNP were determined and an electrocardiogram and echocardiography were performed. Differences between children with and without EV infection were studied. Results: We present results of the first 28 patients included, 14 were EV positive. Basic patient characteristics were similar between EV positive and negative infants. In 17/28 infants cardiac enzymes could be determined. CK was normal in all, CK-MB was elevated in 11 infants, Troponin-I in 2, BNP in 14 and NT-Pro-BNP in all but one. There was no difference in cardiac enzyme concentration between the two groups. Electrocardiograms showed signs of ischemic heart disease in two infants that disappeared at follow-up four weeks later. One was EV positive and one negative. In both cases not enough material was collected to evaluate cardiac enzymes. None of the children showed signs of cardiac dysfunction at echocardiography. Conclusion: Regarding signs of cardiac involvement no differences were found between EV positive and negative infants with sepsis-like illness. Both groups showed elevation of cardiac enzymes. Cardiac involvement seems to be subtle, only 2 infants showed transient ischemia on ECG whereas none showed myocardial dysfunction on conventional echocardiography.